2012
DOI: 10.1021/nl204552v
|View full text |Cite
|
Sign up to set email alerts
|

Colorful InAs Nanowire Arrays: From Strong to Weak Absorption with Geometrical Tuning

Abstract: One-dimensional nanostructure arrays can show fascinatingly different, tunable optical response compared to bulk systems. Here we study theoretically and demonstrate experimentally how to engineer the reflection and absorption of light in epitaxially grown vertical arrays of InAs nanowires (NWs). A striking observation is optically visible colors of the array, which we show can be tuned depending on the geometrical parameters of the array. Specifically, larger diameter NW arrays absorb light more effectively o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
92
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 28 publications
5
92
1
Order By: Relevance
“…One study showed that hemispherical gold nanoparticles on the top of InAs nanowires had a negligible effect on their reflectance spectra. 20 However, in another study, silver, copper, and gold masks on silicon nanowires decreased overall absorption across the solar spectrum. 21 Thus, the role that masks play in optical characteristics is not very clear.…”
Section: Introductionmentioning
confidence: 94%
“…One study showed that hemispherical gold nanoparticles on the top of InAs nanowires had a negligible effect on their reflectance spectra. 20 However, in another study, silver, copper, and gold masks on silicon nanowires decreased overall absorption across the solar spectrum. 21 Thus, the role that masks play in optical characteristics is not very clear.…”
Section: Introductionmentioning
confidence: 94%
“…Specifically, for example, size-quantization and dielectric confinement related to the size (e.g., diameter/length), shape (e.g., taper), and periodicity of the NWs have been engineered for applications in NW-based photovoltaics and photodetectors with considerable success. [21][22][23][24][25][26][27] The versatility of the structure arises from the fact that two fundamental length scales, namely, the extinction distance and the minority carrier diffusion length, can be effectively decoupled in a device with NW arrays. Tapered or stepped structures, including nano-needle nanowires (NNNW) and dualdiameter nanowires (DDNW) have shown enhanced light trapping and absorption, in comparison to nanowires with a uniform diameter along their length.…”
Section: Introductionmentioning
confidence: 99%
“…25 To investigate this diameter dependence of the absorption in detail, electromagnetic modelling using a scattering matrix method 26,27 was performed. In the modelling, cylindrical wires of length L and with diameter d were placed in a square array with pitch p and embedded in a dielectric with a refractive index of n = 1.6 corresponding to the resist.…”
mentioning
confidence: 99%